INTERSEPSI AIR HUJAN PADA TANAMAN KOPI RAKYAT DI DESA KEBET, KECAMATAN BEBESEN, KABUPATEN ACEH TENGAH - Hairul Basri Basri; Manfarizah Manfarizah; Andi Salasa (Jurnal Floratek, 2012)
The purpose of the study was to determine the amount of rainfall interception on coffee plants, and obtain a relationship between rainfall and interception of coffee plant. The research was conducted in a coffee plantation in Kebet Village, Bebesen Sub-District, Central Aceh District. The experiment was carried out from February to March 2011. The method used in this research was a descriptive method, using direct measurements in the field. The samples of coffee plants were 4 years and 15 years old. The results showed that rainfall interception of 4 years-coffee-crop was 56.87% of the total rainfall of 82.50 mm  and  that of 15-year-old coffee plants was 72.12%, of total rainfall of 133.50 mm. The greater the rainfall was, the greater the interception would be, as well as the older age of the coffee plant was, the greater the percentage of interception was recorded. The average proportion of rainfall as the water passes (throughfall) was greater than the proportion of rainfall that becomes stream stems (stemflow), due to high density of leaves covering the stem. Relationship between rainfall and interception on coffee plants was a natural logarithm equation: (1) for 4 years coffee crop,  I = 3.440 ln (Pg) + 0.650 and R2 = 0.56; (2) for 15 years old coffee crop, I = 2.992 ln (Pg) + 2.371 and R2 = 0.69.